Network Visualization: What and How - Stephanie Ritchie; Jessica Sigman (Issues in Science and Technology Librarianship)
The third in a series of columns around data visualizations by three librarians at the University of Maryland (and one collaborator from the U.S. Environmental Protection Agency).